Ride quality analysis of active suspension systems for off-road vehicle - Faried bin Hasbullah (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
In designing passive suspensions, a compromise has to b~ made between ride comfort and car handling. For an off-road vehicle that requires both good ride comfort and good handling capability, a passive suspension alone is not enough. Therefore, there is a need to introduce active elements to further improve vehicle suspensions, which could offer both better ride comfort and car handling to this type of vehicle. This work deals with dynamics and control methods analysis of active suspension systems for off-road vehicles. Comprehensive comparison on three different configurations; 2- axle, 3-axle and 4-axle half-vehicle models were conducted to analyze the effect of using active control methods. The application of two control methods, namely LQR and fuzzy logic controls have been analyzed and compared with passive systems. Sprung mass vertical and pitch acceleration responses were analyzed for measurements of ride quality and road handling. Suspension deflection and tire deflection responses were observed to identify any compromise in the other aspects of vehicle dynamics. Results show that the LQR and FLC successfully controlled the active suspension, improving ride quality and handling of the vehicles without compromising the rattle-space requirement and road holding performance of the vehicles. Comparison of all models also shows that in general, improving ride quality performance will also improve vehicle handling. Moreover, it is observed that FLC control requires less amount of actuator force compared to LQR control to achieve the desired performances.